ABUSUFYAN AKAEV’S WORKS IN ARABIC - Orazaev, Gasan Magomed-Rasulovic; Hanmurzaev, Ismail Ibragimovic (History, Archeology and Ethnography of the Caucasus, 2018)
The article examines writings of the outstanding Dagestani scholar, journalist and poet, religious figure Abu Sufyan Akayev (1872-1931) from the village Nizhnee Kazanische. As an influential representative of Jadid movement at the beginning of the twentieth century, he belonged to the renown Muslim reformers and enlighteners, such as Muhammad ʻAbduh, Rashid Rida, Ismaʻil Gaspraly, ʻAbd al-Rahman Umerov, Qayyum Nasiri, Shihad al-Din Marjani.He wrote works mostly in Kumyk, Arabic, as well as in Azerbaijani and Persian languages. His writings in Arabic are still poorly studied.Some of them appeared in all the 12 issues of the popular magazine on Shariʻa matters of the early Soviet reforms known as Bayan al-haqa᾽iq (1925-1928) whose editor-in-chief he was. He was also the author of articles appeared in some issues of the Arabic-language newspaper Jaridat Dagistan (1913-1918). Some of his letters composed in Arabic are very informative. In addition, Abu Sufyan was the author or compiler of several other publications in Arabic, including a number of booklets devoted to tajwid; multilingual (in 4, 5, 6, 7 languages) dictionaries, in which Arabic vocabulary has always been given in the first place; explanatory-etymological and political dictionaries; several bilingual (Arabic-Kumyk) books.It is noteworthy, that it was Akayev who edited with detailed comments the Arabic book of the well-known Dagestani scholar Hasan Alqadari Divan al-Majnun. Some poetic works created by him in Arabic have been preserved too.Akayev is known as a Katib (copyist) of more than 15 Arabic-language books published in Temir-Khan-Shura, Port-Petrovsk, Bakhchisarai and Simferopol. He is the author of a historical work written in Arabic about the events of the period of the 1917 Revolution and the Civil war in Dagestan.
Keywords: no